Sequential patterns in information systems development an application of a social process model. - Robey, Daniel (ACM transactions on information systems.)
We trace the process of developing and implementing a materials management system in one company over a 15-year period. Using a process research model developed by Newman and Robey, we identify 44 events in the process and define them as either encounters or episodes. Encounters are concentrated events, such as meetings and announcements, that separate episodes, which are events of longer duration. By examining the sequence of events over the 15 years of the case, we identify a pattern of repeated failure, followed by success. Our discussion centers on the value of detecting and displaying such patterns and the need for theoretical interpretation of recurring sequences of events. Five alternative theoretical perspectives, originally proposed by Kling, are used to interpret the sequential patterns identified by the model. We conclude that the form of the process model allows researchers who operate from different perspectives to enrich their understanding of the process of system development.